Introduction to logistics systems management - Ghiani, Gianpaolo, 1967-; Laporte, Gilbert; Musmanno, Roberto, 1965- (Wiley, 2013)
"Introduction to Logistics Systems Planning and Control presents a self contained introduction to the quantitative methods necessary for logistics systems management at a level suitable for students of engineering, computer science and management science. With this new, thoroughly revised edition, the author introduces business logistics and covers sales forecasting, inventory management, warehouse design and management and transport planning and control, and includes new chapters on procurement and the design of automated storage and retrieval systems, as well as new case studies that demonstrate how the methods can be applied to complex logistics problems. It is illustrated throughout by real examples and features a number of new case studies that show the reader how to apply the methods described, and a supporting website features new exercises and teaching material"--Vydavatelská anotace
Obsahuje rejstřík
Keywords: logistika (management); business logistics; učebnice vysokých škol; textbooks (higher)